2007
DOI: 10.1007/s00280-006-0407-2
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of temozolomide by biodegradable polymers is superior to oral administration in a rodent glioma model

Abstract: The survival of tumor-bearing animals was improved with local delivery of TMZ compared with systemic administration. XRT in combination with intracranial TMZ did not cause additional toxicity and prolonged the survival even further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 17 publications
1
69
0
1
Order By: Relevance
“…37 Such a saturation of MGMT would explain the longer survival obtained with protracted and continuous schedules in humans 25 or with increased local brain delivery of TMZ by biodegradable polymers in a rodent glioma model. 4 On the other hand, Jiang et al have recently shown that high doses of CPT-11 may increase the in vivo inhibition of U87 tumor growth in nude mice models. 15 In the same way, some studies suggest that a modest enhancement of either TMZ or CPT-11 may be sufficient to obtain a significant improvement in their antitumoral activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Such a saturation of MGMT would explain the longer survival obtained with protracted and continuous schedules in humans 25 or with increased local brain delivery of TMZ by biodegradable polymers in a rodent glioma model. 4 On the other hand, Jiang et al have recently shown that high doses of CPT-11 may increase the in vivo inhibition of U87 tumor growth in nude mice models. 15 In the same way, some studies suggest that a modest enhancement of either TMZ or CPT-11 may be sufficient to obtain a significant improvement in their antitumoral activity.…”
Section: Discussionmentioning
confidence: 99%
“…28,33 In addition, both clinical and experimental observations confirm that the use of high doses of both TMZ and CPT-11 increase their antitumoral activity. 3,4,15,25,37 For both TMZ and CPT-11, the main limit to high-dose protocols remains the systemic side effects of these drugs. In this context, ultrasound-induced opening of the BBB appears to be an ideal technique that may enhance drug delivery to the brain without having to increase the amount of systemically administered drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its benefit in human GBM patients as an oral chemotherapeutic, TMZ has been described as an ideal candidate for local chemotherapy within the brain given its lack of need for hepatic activation, and its lack of neurotoxicity to normal brain tissue. TMZ rapidly hydrolyzes under normal and alkaline pH, while it is stable at an acidic pH, which is typical of an intra-tumoural environment; this allows TMZ to be taken up into tumour cells where its active metabolite is created, but reduces risk to normal tissues [31]. Because of the desirable properties of PLGA and TMZ and the proven benefit of oral TMZ for human GBM, these two agents were chosen for a local chemotherapy protocol that can be developed as a minimallyinvasive treatment option for primary canine brain tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various chemotherapeutic agents other than BCNU have been exploited to deliver through polymeric system. Preclinical studies demonstrated that many drugs such as temozolomide, paclitaxel, taxotere, and camptothecin were efficacious against gliomas through polymeric delivery (46)(47)(48)(49). Further clinical investigation of the safety and efficacy is therefore warranted.…”
Section: Economic Considerationmentioning
confidence: 99%